(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
The article explores the methodology of integrating innovative technologies in Uzbek language lessons, emphasizing their impact on enhancing students’ linguistic competence, motivation, and engagement. Modern educational tools, such as interactive digital platforms, multimedia resources, and gamified learning applications, are analyzed to demonstrate their effectiveness in creating a dynamic and student-centered learning environment. The study highlights practical approaches for Uzbek language teachers to adopt these innovations, focusing on improving lesson interactivity, facilitating personalized learning, and fostering critical thinking skills. The findings suggest that systematic incorporation of innovative technologies significantly enhances both teaching quality and students’ academic performance in Uzbek language classes.